Model Pembelajaran Project Based Learning (PJBL) yang Ramah Lingkungan dalam Mengurangi Limbah Plastik dan Menerapkan Gaya Hidup Berkelanjutan (Studi Kasus Siswa Kelas 7A SMP Negeri 239 Jakarta Tahun Pelajaran 2022/2023) - Kurnia Septiana (Proceedings Series on Social Sciences & Humanities, 2023)
The research entitled "Environmentally Friendly Project Based Learning (PJBL) Model in Reducing Plastic Waste and Implementing a Sustainable Lifestyle Case Study of Grade 7 Students of SMP Negeri 239 Jakarta Academic Year 2022/2023". Problem limitations, namely (1) What is the Project Based Learning method?; (2) What is the urgency of plastic waste pollution in Jakarta?; (3) What is the concept of a sustainable lifestyle?. The purpose of this study is to analyze the advantages and disadvantages in applying the appropriate Project Based Learning method in social studies learning about environmental pollution and sustainable lifestyles for class VII students of SMPN 239 Jakarta. This method was initiated by the implications of the Minister of Education and Culture Circular No.4 of 2020. Project based learning has the main objective of providing training to students to be more able to collaborate, work together, and empathize with others. Qualitative research methods, and a case study approach for class VII A students at SMPN 239 Jakarta. Collecting data by interviewing and filling out questionnaires via google form. The independent curriculum with P5 (PROYEK PENGUATAN PROFIL PELAJAR PANCASILA) and social studies material for class VII contains learning about environmental pollution which is very urgent to handle, especially in the big city of Jakarta, where plastic waste has caused a lot of concern to the environment and even brought disease to the community. This research supports Governor Regulation (Pergub) Number 142 of 2019 concerning the Obligation to Use Environmentally Friendly Shopping Bags. People are expected to have their own shopping bags for shopping. Schools also support the government program (DKI Jakarta Education Office) regarding the Clean, Green, Organized and Managed Program (BHTT) which encourages students and school officials to bring their own drinking bottles and places to eat from home. The conclusions from this study are that the Project Based Learning Approach has learning steps (syntax) that must be carried out, namely: Starting with the essential question, Designing a plan for the project, create a schedule, create a schedule.